2019
DOI: 10.1007/s42729-019-00034-x
|View full text |Cite
|
Sign up to set email alerts
|

N2O, CH4, and CO2 Emissions from Continuous Flooded, Wet, and Flooded Converted to Wet Soils

Abstract: Fluctuations in soil water content, either anthropogenic or natural, can remarkably influence the C and N pools in arable lands. The dynamics of C and N are directly related in regulation of greenhouse gases (GHGs) emissions. The present study was conducted to explore the effects of water regimes (continuous flooding, continuous wet, and flooding converted to wet) on soil GHGs emissions. Nitrous oxide (N 2 O) emissions from continuous flooding treatment were lower as compared with the continuous wet soil, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Biochar addition to acidic soils enhances soil aeration and O 2 availability in the soil profile and inhibits denitrification by microbes (generally creating suboxic conditions), which in turn decreases N 2 O emissions (Van Zwieten et al 2010). Moreover, biochar has good adsorption properties, and its application results in the adsorption of NH 4 + and NO 3 − on its surface under different water regimes (Pereira et al 2020) and thus decreases the availability of inorganic N pools for nitrifiers and denitrifiers, which produce N 2 O as a byproduct (Singh et al 2010;Clough et al 2013;Khalid et al 2019); thus, this process leads to a substantial reduction in N 2 O production under 50% and 90% WFPS ( Figs. 1 and 5).…”
Section: Discussionmentioning
confidence: 99%
“…Biochar addition to acidic soils enhances soil aeration and O 2 availability in the soil profile and inhibits denitrification by microbes (generally creating suboxic conditions), which in turn decreases N 2 O emissions (Van Zwieten et al 2010). Moreover, biochar has good adsorption properties, and its application results in the adsorption of NH 4 + and NO 3 − on its surface under different water regimes (Pereira et al 2020) and thus decreases the availability of inorganic N pools for nitrifiers and denitrifiers, which produce N 2 O as a byproduct (Singh et al 2010;Clough et al 2013;Khalid et al 2019); thus, this process leads to a substantial reduction in N 2 O production under 50% and 90% WFPS ( Figs. 1 and 5).…”
Section: Discussionmentioning
confidence: 99%
“…Xiao et al (2015) also found that in the soil microbe composition, soil organic carbon fractions (e.g., DOC and MBC) were positively correlated with microbial populations in the Calamagrostis angustifolia wetland. The variation of soil microbes could affect soil carbon loss and soil CO 2 emissions (Allison et al 2010;Carney et al 2007;Khalid et al 2019), further to stimulate carbon sequestration in soil (Six et al 2006). In the respect of the correlation between soil enzyme activity and microorganisms, the significantly positive correlation between them has demonstrated by Groffman et al (2001).…”
Section: Relationship Between Soil Organic Carbon Fractions and Micromentioning
confidence: 97%
“…In the pot experiment, CH 4 emissions from CM:SS (1:1.5) were lower than that from the other CM:SS treatments, possibly due to the lower organic C content (5.51 gC m −2 ) than CM:SS (1:1) (5.78 gC m −2 ) and CM:SS (1:2.5) (5.63 gC m −2 ). Organic C can provide C as an energy source for methanogenic bacteria to produce CH 4 [14]. Organic C is an important factor affecting CH 4 production capacity, and the readily decomposed organic matter in paddy fields increases CH 4 emissions under an anaerobic environment [15].…”
Section: Ghg Emissions In the Incubation And Pot Experimentsmentioning
confidence: 99%